'Cairo Ring Road': Anthony Hamboussi's Poetic Survey of an Urban Topography. (1st July 2016) - Elshahed, Mohamed
Cairo's landscape has morphed over the past century due to uncontrolled urban growth. This transformation has overturned the city's iconic status as a city of great monuments of Islamic art, the 'City Victorious'. While Cairo has occupied a central position in the study of historic art and architecture from the Middle East, poor planning and mismanagement of heritage sites have put the city's historic significance into a state of crisis. While historians turn away from Cairo's contemporary urbanity, by contrast, photographers such as Anthony Hamboussi have refocused their lenses on the city's current realities. The city's historic monuments are drowning in an urban topography that resulted from impoverished governance and improvised urban expansion. What can we learn from photographs of Cairo's ongoing urban informality, uneven development and spatial inequality? This article critically examines one photographer's project to make visible the undesirable majority of contemporary Cairo. The author argues that engaging with the city's contemporary reality, in this case through photography, is key to understanding its declining heritage status and the poor condition of many of its monuments of Islamic architecture.